PENGARUH KUALITAS PRODUK, PROMOSI, FAKTOR SOSIAL DAN FAKTOR PSIKOLOGI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC YAMAHA MIO (STUDI PADA YAMAHA AGUNG MOTOR SEMARANG) - Yunita Sawitri; Wahyu Hidayat; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2013)
This research aimed to find out how much influence of Behaviour consumer towards Buying decision of Yamaha Mio in Yamaha Agung Motor Semarang. Research type which used in this eksplanatory research. Sampling techniques using purposive sampling, by distributing  questionaries to 94 respondents. Data analysis using quantitative analysis, validity control, reliability, data normality, muliticollinearity, heteroskedasticity, simple linear regression, double linear regression, coefficient determiasi, t test and f test with SPSS program. The result of statistical analysis know simple linear regretion equation between Product Quality and Buying Decision was Y  =   -0,286 + 0,340 X1. For Promotion (x2) with Buying Decision the equality was Y  =   -0,206 + 0,434 X2. For Social Factor (x3) with Buying Decision , the equality was 2,979 + 1,117 X3. For Psychological Factor (X4) with Buying Decision , the equality was Y = 1,645 + 0,858. Simultaneously influence of Product Quality, Promotion, Social Factor, and Psychological Factor towards Buying Decision be see using double liniar analysis the result was Y = -1,026 + 0,115 X1 + 0,139 X2 + 0,336X3 + 0,190X4. The can see from the value of the coeficient of determiation as 0,851 shows that variables have positive influece. That means the iflueces of Product Quality variable, Promotion variable, Social Factor variable, and Psychological Factor variable towards Buying Decision of 85,1 percent, while the rest 14,9 percent influeced by others variable. Suggestion that can be delivered to Yamaha Agung Motor is to provide a more satisfactory service workshop for customers and giving quality spare part of yamaha matic mio from yamaha factories to show up their quality products. Hopefully Yamaha Agung Motor customers can get alot of information about Yamaha Mio Matic motorcycle and they want to have it as well as the promotion. It’s better if Yamaha Agung Motor could give their customer information on television comercial, because most of our people spent their time by watching television.